Health-seeking behavior and compliance to post exposure prophylaxis among animal bite victims in India - Ravish Shankaraiah Haradanhalli; Hulawadi Shivalingaiah Anwith; Banandur S Pradeep; Shrikrishna Isloor; Gangaboraiah Bilagumba (Wolters Kluwer Medknow Publications, 2019)
Background: In rabies endemic countries, where every animal bite is potentially a suspected rabid exposure, the exposed individuals should seek early and proper health care. It is also essential to complete the full course of postexposure vaccination to protect against rabies. Objectives: The study aimed at determining the health-seeking behavior of animal bite victims; assessing the perceived risk of rabies transmission from different animals and knowledge on its prevention and finding out the compliance to complete course of rabies vaccination and associated factors. Methods: A multi-centric, health facility-based survey was conducted during May 2017 to January 2018 in six regional-representative states involving 18 health facilities. Study participants were animal bite victims attending the health facilities. The data from all the study participants across the country were compiled and analyzed using descriptive statistics and Chi-square test to find out the association of factors influencing compliance. Results: Among a total of 529 animal bite victims, 83.6% sought postexposure prophylaxis coming directly to health facility; others visited nonallopathic/traditional healers/veterinarians/Auxiliary Nursing Midwifery before coming to health facility. The perceived risk of disease transmission and knowledge on the prevention of rabies was insufficient among the exposed victims. All participants were started with anti-rabies vaccination; the compliance rate for the full course of intramuscular rabies vaccination was 65.9% and for intra-dermal rabies vaccination, it was 85.1%. Among Category III exposures, only 46.2% received rabies immunoglobulin. Conclusions: Health-seeking behavior and compliance to complete course of anti-rabies vaccination is unsatisfactory, which has to be improved to prevent rabies.